Reflections on vocational guidance and counselors' training in contexts of global change - Müller, Marina (1999)
Vocational guidance (V.G.) is currently facing both theoretical and methodological reconsiderations. This demands rethinking ethical and scientific assumptions, counselors' role and training. V.G. provides a space to receive information about oneself as well as about labor world and for the elaboration of projects for the future. Many guidance situations in teenagers and young adults are described in this paper, highlighting the main current emergent aspects. There was a remarkable protagonism of those seeking guidance and the reflective frame of the guidance. This frame prepares for the educational stage changes and also for occupational insertion working on aspects that widen autonomous choice and the development of social abilities and attitudes to carry out the vocational project and the development in work. Troubled sociocultural and economic transformations demand an on-going training on the part of counselors. To that end, possible fields of concern and subjects to be worked in said training are suggested.